Method Modification of Developing Ischemic Stroke Animal Models Using Intravenous Catheters in Rats - Perdhana, Ika Satya; Handharyani, Ekowati; Darusman, Huda Shalahuddin; Nugroho, Setyo Widi; Maheshwari, Hera; Fitri, Arni Diana (Acta VETERINARIA Indonesiana, 2025)
In various parts of the world, including Indonesia, the incidence of ischemic stroke remains high, and its impact poses a significant burden. This condition is influenced by numerous limitations in ischemic stroke therapy. Research on ischemic stroke is therefore crucial to develop, making the creation of appropriate animal models a vital necessity. One of the most commonly used methods by researchers to create animal models is the Middle Cerebral Artery Occlusion (MCAO) method. However, in Indonesia, its application remains limited due to the lack of available facilities. Method modifications can be implemented to enable the development of animal models in Indonesia. This study employed modifications to the MCAO method on eight Sprague Dawley rats. The modification involved using an intravenous catheter to facilitate the insertion of the filament as an occluder in the middle cerebral artery of the rats. Based on clinical and pathological observations, it can be concluded that the modified MCAO method used in this study is suitable for creating ischemic stroke animal models. With this modification, the creation of ischemic stroke animal models can be carried out in a simpler and more cost-effective manner.